On charm production near the phase boundary - Braun-Munzinger, Peter; Stachel, Johanna (Arxiv, 2001)
We discuss aspects of the statistical hadronization model for the production of mesons with open and hidden charm in ultra-relativistic nuclear collisions. Emphasis is placed on what can be inferred from the dependence of the yield of charmonia on the number of participants in the collisions.
Gesehen am 26.02.2020